Spatiotemporal distribution patterns of soil ciliate communities in the middle reaches of the Yarlung Zangbo River - Huang, Qian; Li, Mingyan; Li, Tianshun; Zhu, Shiying; Wang, Zhuangzhuang; Pu, Bu (Frontiers in Environmental Science, 2024)
Soil ciliates, as protozoa, play a crucial role in biogeochemical cycling and the soil food web, yet they are highly sensitive to environmental fluctuations in soil conditions. A total of 290 soil samples were collected from four habitat types of grassland, shrubland, forestland and wetland in the middle reaches of the Yarlung Zangbo River during the wet and dry seasons, and 138 species of ciliates were identified.In total, we identified 138 ciliate species across two seasons and four habitat types in middle reaches of the Yarlung Zangbo River. Soil ciliate alpha diversity exhibited greater variation across habitat types than seasons. Moreover, soil ciliate diversityalpha diversity was higher during the wet season compared to the dry season, with the wetland habitat showing the highest diversity and the grassland habitat displaying the lowest. We observed spatiotemporal heterogeneity in the composition of soil ciliate communities across different seasons and habitat types. Notably, Litostomatea, Karyorelictea, and Prostomatea predominated in ciliate communities during the wet season and in grassland habitat. Phyllopharyngers dominated during dry seasons and in forested regions, while Spirotrichea species were prevalent in wetland and forested areas. The cooccurrence network analysis showed that soil ciliate community was more complex in wet season than in dry season, and the stability of soil ciliate community in wet season was higher than that in dry season. The stability of soil ciliate community in wetland was higher than that in forestland, shrubland and grassland, and the anti-interference ability was stronger. Soil temperature (ST), Total nitrogen (TN), Soil organic matter (SOM) and Soil water content (SWC) are important factors affecting the structure of soil ciliate community. By influencing the metabolic rate and nutrient acquisition of soil ciliates, the distribution pattern of soil ciliate community diversity in the middle reaches of Yarlung Zangbo River is shaped. Among the environmental factors, soil water content(SWC), soil organic matter (SOM), and vegetation cover (VC) were found to be correlated with spatiotemporal differences in soil ciliate communities. Co-occurrence network analysis revealed that soil ciliate communities in the Yarlung Zangbo River displayed significantly greater complexity during the wet season compared to the dry seasons.